Let's substitute them to the Maxwell’s equations (with no charges and currents in vacuum):
"\\nabla\\cdot\\mathbf{D}= 0\\\\\n\\nabla\\cdot\\mathbf{B}=0\\\\\n\\nabla\\times\\mathbf{E}=-\\frac{\\partial\\mathbf{B}}{\\partial t}\\\\\n\\nabla\\times\\mathbf{H}= \\frac{\\partial\\mathbf{D}}{\\partial t}" Considering the fact that "\\mathbf{D} = \\varepsilon_0\\mathbf{E}" and "\\mathbf{B} = \\mu_0\\mathbf{H}", obtain:
1.
"\\nabla\\cdot\\mathbf{D}= \\varepsilon_0 \\left ( \\dfrac{\\partial E_x}{\\partial x} +\n\\dfrac{\\partial E_y}{\\partial y}+\n\\dfrac{\\partial E_z}{\\partial z} \\right)" As far as "\\mathbf{E} = (0,E_m\\sin(x)sin(t),0)", y-coordinate does not depend on y, so the divergence is equal to 0: "\\nabla\\cdot\\mathbf{D}=0". The first equation is satisfied.
2. Similarlly, as far as "\\mathbf{H} = (0,0,E_m\/\\mu_0 \\cos(x), \\cos(t))", the z-coordinate does not depend on z, thus, the divergens will be equal to 0: "\\nabla\\cdot\\mathbf{B} = \\nabla\\cdot\\mathbf{H}=0". The second equation is satisfied.
3. The curle is:
"\\nabla\\times\\mathbf{E}= \\left(\\frac{\\partial E_z}{\\partial y} - \\frac{\\partial E_y}{\\partial z}\\right) \\mathbf e_x+\n\\left(\\frac{\\partial E_x}{\\partial z} - \\frac{\\partial E_z}{\\partial x}\\right) \\mathbf e_y+\n\\left(\\frac{\\partial E_y}{\\partial x} - \\frac{\\partial E_x}{\\partial y}\\right) \\mathbf e_z" From all these derivatives only "\\dfrac{\\partial E_y}{\\partial x}" will not be equal to 0. Let's calculate it:
"\\dfrac{\\partial E_y}{\\partial x} =E_m\\sin(t)\\dfrac{\\partial }{\\partial x}\\sin(x) = E_m\\sin(t)\\cos(x)" Thus:
"\\nabla\\times\\mathbf{E}= (0,0,E_m\\sin(t)\\cos(x) )" On the other hand:
"-\\dfrac{\\partial\\mathbf{B}}{\\partial t} =-\\mu_0\\dfrac{\\partial\\mathbf{H}}{\\partial t}= \n\\left(0,0, - \\dfrac{\\partial}{\\partial t} [E_m \\cos(x), \\cos(t)] \\right)=\\\\\n=(0,0, E_m\\sin(t)\\cos(x))" Thus, "\\nabla\\times\\mathbf{E}=-\\frac{\\partial\\mathbf{B}}{\\partial t}" and the third equation is also satisfied.
4. The curle is:
"\\nabla\\times\\mathbf{H}= \\left(\\frac{\\partial H_z}{\\partial y} - \\frac{\\partial H_y}{\\partial z}\\right) \\mathbf e_x+\n\\left(\\frac{\\partial H_x}{\\partial z} - \\frac{\\partial H_z}{\\partial x}\\right) \\mathbf e_y+\n\\left(\\frac{\\partial H_y}{\\partial x} - \\frac{\\partial H_x}{\\partial y}\\right) \\mathbf e_z" From all these derivatives only "-\\dfrac{\\partial H_z}{\\partial x}" will not be equal to 0. Let's calculate it:
"-\\dfrac{\\partial H_z}{\\partial x} =-E_m\/\\mu_0\\cos(t)\\dfrac{\\partial }{\\partial x}\\cos(x) =E_m\/\\mu_0\\cos(t)\\sin(x)" Thus:
"\\nabla\\times\\mathbf{H}= \\dfrac{1}{\\mu_0} (0,E_m\\cos(t)\\sin(x),0)" On the other hand:
"\\dfrac{\\partial\\mathbf{D}}{\\partial t} =\\varepsilon_0\\dfrac{\\partial\\mathbf{E}}{\\partial t}= \n\\varepsilon_0\\left(0, \\dfrac{\\partial}{\\partial t} [E_m \\sin(x), \\sin(t)],0 \\right)=\\\\\n=\\varepsilon_0(0,E_m\\cos(t)\\sin(x),0)" Because of the coeffitients "\\dfrac{1}{\\mu_0}" and "\\varepsilon_0" the right hand side is not equal to the left hand side:
"\\nabla\\times\\mathbf{H}\\ne \\frac{\\partial\\mathbf{D}}{\\partial t}"
Thus, the fourth equation is NOT satisfied.
Answer. These fields do not satisfy Maxwell’s equations.
Comments
Leave a comment